SOCIAL SUPPORT, SELF-EFFICACY, AND STUDENT’S MENTAL HEALTH IN ONLINE LEARNING DURING PANDEMIC - Sriwiyanti, Sriwiyanti; Saefudin, Wahyu; Shofia, Adinda; Mujib, Mujib (al-Balagh : Jurnal Dakwah dan Komunikasi, 2022)
The Covid-19 pandemic influenced education policy in Indonesia; the consequence of traditional learning switched to online learning. This transition affects students’ mental health at various universities in Indonesia. This study aimed to examine the mental health level of 82 students who took online learning course and explained the effect of social support and self-efficacy on students’ mental health. The present study utilized three measuring tools namely the Indonesian versions of Child and Adolescent Social Support Scale (CASSS), General Self-Efficacy Scale, and Mental Health Continuum (MHC-SF). Regression analysis was used to determine the effect of social support and self-efficacy on students’ mental health. The results obtained from this study were that the majority of respondents’ mental health, 81.7% were in the high category, 17.1% were in the moderate category, and 1.2% of respondents were in the low category. Furthermore, social support and self-efficacy also affect 71.9% (R Square = 0.719, p = 0.000) of mental health, with an effective contribution of 41.9% by social support and 30% by self-efficacy. Thus, social support and self-efficacy are important keys to improving students’ mental health in online learning.